Spin-Off Impact on Islamic Banking Performance: A Comparative Analysis: Dampak Spin-Off terhadap Kinerja Perbankan Syariah: Analisis Komparatif. - Andrian Prawira Yudha; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the financial performance of a prominent Islamic bank before and after a spin-off, employing a Paired Sample T-Test with SPSS 25. The dataset spans three years pre-spin-off and three years post-spin-off. The research reveals significant disparities in several financial indicators: Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Finance to Deposit Ratio (FDR), Return On Assets (ROA), and Operational Expenses to Operational Income (BOPO). These findings shed light on the profound implications of the spin-off on the bank's financial performance, offering valuable insights for practitioners and policymakers in the Islamic banking sector. Highlight: Spin-Off Impact: Explore the effects of a corporate spin-off on Islamic bank financial performance. Statistical Analysis: Utilize Paired Sample T-Test to rigorously assess pre- and post-spin-off financial data. Strategic Insights: Gain valuable insights into the implications of spin-offs for the Islamic banking industry. Keywords: Spin-Off, Islamic Banking, Financial Performance, Paired Sample T-Test, Comparative Analysis